2013
DOI: 10.4103/2277-9531.115840
|View full text |Cite
|
Sign up to set email alerts
|

Health promoting Hospitals in Iran: How it is

Abstract: Background:The World Health Organization (WHO) produced the Ottawa Charter for Health Promotion (HPH) back in 1986. Then expressed the Budapest Declaration of Health Promoting Hospitals and after determined standards for reorienting hospitals towards health promotion So, this study evaluated Iranian hospitals based on WHO-HPH standard.Materials and Methods:This study was a descriptive - analytical survey in selected hospitals of Iran (38 hospitals from 5 provinces). Method of data collecting was through review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
(35 reference statements)
5
26
0
Order By: Relevance
“…The results of the present study showed that total scores of the intervention hospital of the standards of health promoting hospitals was 72.26±4.1 (out of 80) While the hospital evaluated in the study of Lin et al[20] obtained the score of 73.12 (out of 100) and the hospitals in the study of Groene et al [6] achieved the score of 71.9± 25 (out of 136) and the score of the hospitals examined in the study by Yaghoubi et al [7] was54.1 ± 15.1 (out of 136) and score of hospitals surveyed in the study of Lin et al[10] was 76.26 (out of 100);therefore, the score of hospital surveyed in this study was higher than the hospitals in the above-mentioned studies. In the Lin study in Taiwan [10] a cross-sectional survey of all Taiwan’s hospitals above the local community hospital level was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the present study showed that total scores of the intervention hospital of the standards of health promoting hospitals was 72.26±4.1 (out of 80) While the hospital evaluated in the study of Lin et al[20] obtained the score of 73.12 (out of 100) and the hospitals in the study of Groene et al [6] achieved the score of 71.9± 25 (out of 136) and the score of the hospitals examined in the study by Yaghoubi et al [7] was54.1 ± 15.1 (out of 136) and score of hospitals surveyed in the study of Lin et al[10] was 76.26 (out of 100);therefore, the score of hospital surveyed in this study was higher than the hospitals in the above-mentioned studies. In the Lin study in Taiwan [10] a cross-sectional survey of all Taiwan’s hospitals above the local community hospital level was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps one of the reasons is the small size and limited space of the hospital which, despite the small number of staff and limited physical environment, made the implementation of health promotion standards easier. However, in the study of Lin et al [20] and Yaghoubi et al [7], the highest scores were in the standard of patient information and intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other WHO health promotion programs, such as health promotion hospital (HPH), which considers education and health promotion of clients, staff, organization, and community (39,40), multidimensional education can be integrated in Iran. On the other hand, new methods of education, such as use of mobile phones and social networks, are suggested to improve evidence-based education in the future.…”
Section: Discussionmentioning
confidence: 99%